Thromboresistant and rapid-endothelialization effects of dopamine and staphylococcal protein A mediated anti-CD34 coating on 316L stainless steel for cardiovascular devices. Issue 13 (7th April 2015) - Chen, Jialong; Li, Quanli; Xu, Jianguang; Zhang, Le; Maitz, Manfred F.; Li, Jun
<x xml:space="preserve">Abstract</x> The oriented immobilization surface of anti-CD34 antibodies displayed excellent affinity for EPCs and good anticoagulation performance.